Squeezing properties of nondegenerate three-level laser with degenerate parametric amplifier - Getahun, Misrak; Salih, Edris (International Journal of Physical Research, 2021)
We study the squeezing properties of the light generated by nondegenerate three-level laser in which the three-level atoms are in cascade configuration with degenerate parametric oscillator. We obtain the c-number Langevin equations associated with the normal ordering using the pertinent master equation. Making use of the solutions of the c-number Langevin equations, we calculate the quadrature variances. The results show that the two-mode light produced by the system under consideration is in squeezed state and the squeezing occurs in the minus quadrature. The degree of squeezing increase with the linear gain coefficient and almost perfect squeezing can be obtained for large values of the linear gain coefficient and the atoms initially prepared in lower level slightly greater than in the upper level. Moreover, the presence of nonlinear crystal increases the degree of squeezing for single mode and two-mode lights.Â Â Â